2014
DOI: 10.1074/jbc.m114.597682
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Screen Identifies Small Molecule Inhibitors Specific for Mycobacterium tuberculosis Phosphoserine Phosphatase

Abstract: Background: Phosphoserine phosphatase (PSP) is an essential enzyme involved in L-serine biosynthesis. Results: High throughput screen was performed to identify specific PSP inhibitors with activity against intracellular bacteria. Conclusion: Validation of PSP as a drug target would lead to identification of scaffolds with a novel mechanism. Significance: This is the first report demonstrating selective inhibition of M. tuberculosis PSP enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 56 publications
(48 reference statements)
2
30
0
Order By: Relevance
“…Greater clorobiocin efficacy may be the result of stronger enzyme inhibition by clorobiocin as previously shown against the DNA gyrase and topoisomerase IV proteins from both E. coli and Staphylococcus aureus [21]. Alternatively, differences between novobiocin and clorobiocin might be due to other clorobiocin targets, for example clorobiocin can inhibit the phosphoserine phosphatase SerB2 of Mycobacterium tuberculosis while novobiocin cannot [22].…”
Section: Discussionmentioning
confidence: 99%
“…Greater clorobiocin efficacy may be the result of stronger enzyme inhibition by clorobiocin as previously shown against the DNA gyrase and topoisomerase IV proteins from both E. coli and Staphylococcus aureus [21]. Alternatively, differences between novobiocin and clorobiocin might be due to other clorobiocin targets, for example clorobiocin can inhibit the phosphoserine phosphatase SerB2 of Mycobacterium tuberculosis while novobiocin cannot [22].…”
Section: Discussionmentioning
confidence: 99%
“…Initially characterized as an enzyme involved in the dephosphorylation of O-phospho-L-serine to L-serine [31], MtSerB2 has been recently shown to be secreted into the cytoplasm of infected THP1 cells and is hypothesized to help the bacterium in immune invasion and evasion [30]. SerB2 belongs to the haloacid dehalogenase (HAD) class of enzymes.…”
Section: Serb2mentioning
confidence: 99%
“…In the first report on MtSerB2, Arora et al [31] biochemically characterized the enzyme and showed that MtSerB2 displayed a preference toward O-phospho-L-serine over O-phospho-L-threonine. Through high throughput screening using 2300 compounds, they identified Clorobiocin and Rosalinine as the specific inhibitors against MtSerB2.…”
Section: Serb2mentioning
confidence: 99%
“…Earlier studies have also shown that MtSerB2 represents a new druggable target [5,28]. As part of evaluation of compounds from the Prestwick Chemical Library, we prioritized studies on Clofazimine (CFZ), based on ongoing and reported evaluation of riminophenazine analogs by the TB alliance and other studies, against MDR and XDR TB infection [9].…”
Section: Identification Of Clofazimine (Cfz) As a Potent Inhibitor Ofmentioning
confidence: 99%